PENGARUH METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS ANAK USIA 5-6 TAHUN - Syahrul, Fitrah Saputri; Kartini , Marzuki; Rika, Kurnia (Ihya Ulum: Early Childhood Education Journal, 2023)
This study describes the science process skills of students, namely the skills of observing, predicting and communicating the results of color combination experiments. The type of research used is quantitative research quasi experiment with the research design used by researchers is pretest-posttest control group design. The subjects in this study were Aisyiyah Mamajang Kindergarten students in Makassar City in classes B2 and B3. The results of this study showed that children's science process skills in the experimental group at meetings I to III had increased, namely from 15 children in the experimental group as many as 1 child or 6.7% were in the category of developing as expected and as many as 14 children or 93.3% were in the category of developing very well. The conclusions of this study are: 1) The science process skills of students in the experimental group before the application of the experimental method at Aisyiyah Mamajang Kindergarten, Makassar City are still very low, after the application of the experimental method, the science process skills of children in the experimental group have increased significantly. 2) There is an effect of the application of effective experimental methods on the science process skills of students at Aisyiyah Mamajang Kindergarten, Makassar City.